A Review Paper on El Nino (International Journal of Innovative Research in Engineering & Management, 2023)
El Nino episodes are major climatic  disruptions that occur every 2 to 8 years and originate in  the equatorial Pacific Ocean. From the coastlines of Peru  and Ecuador to the middle of the equatorial Pacific  Ocean, unusually warm waters at the ocean surface mark  the developed phase of El Nino. The reason of this  occurrence is a peculiar lessening of the westward  blowing trade winds, which enables warm surface waters  to reverse their course eastward. El Nino's climatic effects  are increasing throughout the globe, and this may have a  variety of consequences on regional weather. It is linked  to a broad range of changes in the climate system, and it  has the potential to have significant socio-economic  consequences in the infrastructure, agricultural, health,  and energy sectors. Despite the fact that El Nino occurs in  the tropical Pacific, it has an effect on worldwide climate  and weather events such as drought, floods, and tropical  storms. The usual state in the equatorial Pacific has  altered because of increased greenhouse gas emissions,  which has resulted in changes in the El Nino Southern  Oscillation (ENSO). ENSO fluctuations will continue to  exist and affect global climate conditions in the future  decades and millennia, we can be certain. As a result,  both scientists and the public rely on predicting and  understanding ENSO conditions. The occurrence of El  Nino and its effect on world climate and socio-economic  status have been researched and discussed in this article.
Keywords: Climate; Drought; El Nino; ENSO; Trade winds